Optimising cutinase enzyme recovery in thermo-induced phase separation of LS54/DX ATPS by enhanced volume exclusion effect - Fariza Akmal Abdul Mutalib; Jamaliah Md Jahim; Abdul Wahab MohammadDepartment; Farah Diba Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2018)
Low recovery of cutinase enzyme in water-enriched phase after thermo-induced separation stage of LS54/Dx aqueous two-phase system was improved by enhanced volume exclusion effect in the polymer-water extraction system. It was done by increased the polymer concentration in the polymer-water system. After primary phase separation, more LS54 (polymer) which is the system’s component itself were added into polymer-enriched phase and mixed thoroughly before thermo-induced separation step proceeded. The compositions of LS54 added into the polymer-enriched phase were 0.25, 0.5 and 0.75 g LS54/g top phase. The thermo-induced phase separation was carried out at 37°C. It was found that cutinase recovery in water-enriched phase was increased up to 5-13% with the increment of polymer concentration in the system as compared to a system without polymer addition. The optimum concentration obtained for the polymer added was 0.5 g LS54/g top phase whereby it attained 82% recovery of cutinase enzyme in water-enriched phase after thermoseparation step. Although the increment of enzyme recovery was not exceptionally high as compared to another method such as adding ligand, an affinity tag or neutral salt, still this method is applicable because of its more straightforward work, polymer recycle capability, and enzyme recovery in water phase would definitely give benefit to further downstream processing.